Cheap 3D scanner - Tan, Raphael Yi Wei (2014)
Ever since the Microsoft Kinect was first revealed at the Electronic Entertainment Expo 2009, it has captured the imagination of the world with the potential applications that could arise with a device that could not only process environmental information in 3D, but also affordable enough to be a commonplace household item.